Analysis of Errors in Solving Numeracy Problems Based on the Newman Procedure, Viewed from the Metacognition Levels of Fifth-Grade Elementary School Students - Listiyani Listiyani; Oneng Fitriani; Siti Apsoh; Atot Sugiri (Universitas Negeri Surabaya, 2026)
Student errors in solving numeracy problems often stem not only from cognitive limitations but also from low metacognitive awareness regarding the planning, monitoring, and evaluation of thought processes. This study aimed to describe the metacognition levels of fifth-grade students at State Elementary School Gunung Sunda, as well as the types and stages of errors committed—based on Newman's Procedure—at each metacognition level. A qualitative descriptive approach was employed, involving three subjects selected purposively to represent high, medium, and low metacognition categories, determined through the triangulation of observations, interviews, and test answer sheets. The results indicate that the distribution of student metacognition was dominated by the low category. The student with high metacognition committed only a minor encoding error, with no errors at other stages. The student with medium metacognition exhibited inconsistent patterns: active monitoring but incomplete evaluation on one problem, and cumulative errors across five stages on another problem due to a reading error. The student with low metacognition experienced all five types of Newman's errors, resulting from the simultaneous absence of the three metacognitive components.